Kelas BTQ sebagai Inovasi Kurikulum PAI dalam Memberantas Buta Huruf Al-Qur’an Siswa MAN 2 Karanganyar - Hanani, Hanif; Sugiyarti, Sri (Darul Yasin Al Sys, 2024)
This research focuses on the BTA class as an innovation of the PAI curriculum to eradicate the al-Qur’an letter blindness in MAN 2 Karanganyar. The BTA class program is in response to the search of PAI teachers against students and pupils who are not able or not smooth in reading the Qur'an so affecting their level of understanding in PAI subjects. This method of research uses qualitative descriptive research that explains what is happening in accordance with the facts on the field. Data collection techniques are done through observation, documentation and interviews. The results of the research show that the innovation of the PAI curriculum, i.e. the establishment of this BTA class, has a very positive impact on students. With this BTA class, students who are inadequate or unable to read the Qur'an can be helped especially in understanding religious subjects. The Quran is the most important part of the Qur'an. Another positive impact is that it can increase the level of confidence of students as graduates of the madrasah who are viewed by the community as people who are committed in the field of religion and of course in terms of reading the Qur'an.